The ADR Market and the Effects of ADR Issue on the Underlying Security; a Survey - Parisi, Franco (Estudios de Administración, 1996)
The present paper exposes the definition and main characteristics of American depository receipts (ADR) and their market. The research discusses the theoretical and practical explanations of the ADR demand by us investors. It also considers, in theoretical terms, the reasons why an international issue would imply changes in the return and variance of the underlying security of ADRS, and comments on the evidence related t to such an issue. The main conclusion of this paper is addresed to the impact on the underlying security following the international listing by middle-sized firms from semi-integrated capital markets.